2021
DOI: 10.3390/en14165112
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Global Long-Term EROI of Gas: A Net-Energy Perspective on the Energy Transition

Abstract: Natural gas is expected to play an important role in the coming low-carbon energy transition. However, conventional gas resources are gradually being replaced by unconventional ones and a question remains: to what extent is net-energy production impacted by the use of lower-quality energy sources? This aspect of the energy transition was only partially explored in previous discussions. To fill this gap, this paper incorporates standard energy-return-on-investment (EROI) estimates and dynamic functions into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 80 publications
(92 reference statements)
0
8
0
2
Order By: Relevance
“…The sensitivity of non-renewable EROIs to the fuel-embodied energy requirements is a discussion that emerges in EROI studies due to its ability to change their EROI trends 17 , 43 45 . The core of this sensitivity analysis relates to the natural gas and oil consumption during the ET.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of non-renewable EROIs to the fuel-embodied energy requirements is a discussion that emerges in EROI studies due to its ability to change their EROI trends 17 , 43 45 . The core of this sensitivity analysis relates to the natural gas and oil consumption during the ET.…”
Section: Resultsmentioning
confidence: 99%
“…SSPs should be used with caution since important criticisms of overestimation of economic growth and CO2 emissions of SSP3 and SSP5 have been adressed (Burgess et al 2020;Pielke and Ritchie 2021;Pielke Jr et al 2022). Since long-term decoupling between energy consumption and economic growth seems impossible (Huang et al 2008;Haberl et al 2020;Hickel and Kallis 2020;Andrieu et al 2022) and the likeliness of all-oil liquids peak in the next 15 years (Delannoy et al 2021a;Laherrère et al 2022) and gas before 2050 (Delannoy et al 2021b), the plausibility of scenarios with continuous economic growth in the 21 st century seems low, as pointed out by Steckel et al (2013). Therefore, additional efforts are needed to have access to a wider range of post-growth scenarios (Hickel et al 2021;Keyßer and Lenzen 2021;Lenzen et al 2022), building upon the propositions of Nieto et al (2020) and Bodirsky et al (2022) which focus only on energy infrastructures and the food sector, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of recent papers agreed on the necessity of reducing energy consumption by society in the coming years Aghahosseini et al (2019); Slameršak et al (2022); King and Van Den Bergh (2018); Vidal, Olivier et al (2018); Valero et al (2018); Delannoy et al (2021a); . Solé et al (2018) alerts that if the global society continues to keep increasing their final energy consumption by 3% each year, an 8% annual rate of RE deployment is required, which is higher than the 6% annual rate observed in the last century (as calculated from data in Ritchie et al ( 2022)).…”
Section: Demand and Renewable Energy Capacity Deployment Projectionsmentioning
confidence: 99%
“…Another limiting factor, highlighted previously, is the energy required to make transition possible, which would not be available to society towards demand satisfaction. This amount is expected to be considerable Slameršak et al (2022); Sers and Victor (2018); Delannoy et al (2021a). This phenomenon, referred to as energy cannibalism, has been analysed in several papers, Slameršak et al (2022); Sers and Victor (2018); Capellán-Pérez et al (2019); IEA (2010), all of which have concluded that it would be unrealistic to increase the energy needed for RE deployment without reducing energy available to society IEA (2010); Sers and Victor (2018).…”
Section: Demand and Renewable Energy Capacity Deployment Projectionsmentioning
confidence: 99%